Detection of Partial Deletions of Y-chromosome AZFc in Infertile Men Using the Multiplex Ligation-dependent Probe Amplification Assay - DJ Bunyan; JLA Callaway; N Laddach (JRI, 2012)
Background: In recent studies, partial deletions of the azoospermia factor c region (AZFc) on the Y-chromosome have been detected in males with infertility problems. However, there has been a lot of debate about their significance. In order to study such deletions, a simple but accurate method for their detection was applied in this study. Methods: We present data obtained from the Multiplex Ligation-dependent Probe Amplification (MLPA) assay using a new Y-chromosome-specific MLPA probemix (P360) which allows the easy detection of partial AZFc deletions. Results: Partial AZFc deletions were detected in 8% of our cohort of previously mutation-negative infertile males (and 0% of the fertile control cohort). Conclusion: These results provide further evidence of the causality of partial AZFc deletions. None of the partial AZFc deletions were detectable by the standard multiplex PCR method, demonstrating the advantage of the MLPA method.
Keywords: Causality, Gene dosage, Infertility, Microdeletions, Molecular genetics, Y-Chromosome